Pemanfaatan Mikofer pada Kelapa Sawit dengan Interval Penyiraman di Pembibitan - Sakra Damanik; Irsal Irsal; Yaya Hasanah (Jurnal Agroekoteknologi, 2015)
The availability of water that is limited for watering during the dry season, especially in the largearea of oil palm nursery can be overcome by saving the water, which, in this research is the intervalwatering. Another alternative that can be applied is the utilization of mycofer. The research wasconducted in the greenhouse of the Faculty of Agriculture University of North Sumatra fromSeptember 2013 to January 2014. Research design was factorial randomized block design with twofactors : mycofer application (0, 5, 10, 15 g/seedling) and the interval watering (every day, threedays and five days). Parameters observed were percentage of root infection, leaf area total, dryweight of shoot, dry weight of root, and water use efficiency (WUE). The result showed thatmycofer application significantly affected the percentage of root infection which the highestinfection on 18th week after application was 28,89% as the result of 10 grams mycofer application.There was no significant effect of both mycofer application and watering interval in leaf area total,dry weight of shoot and root. Watering interval significantly affected the WUE which the highestWUE was 13,69% as the result of five days watering interval. Moreover, the watering interval forfive days in the research didn’t impair the oil palm growth within 18 weeks. The interaction had nosignificant effect on all of the parameters observed.Keywords: mycofer, watering interval, oil palm